Association between drug tolerability and medical resource use in prophylaxis of invasive fungal infections after allogeneic hematopoietic stem cell transplant. (17th June 2013) - Gao, X.; Marks, D. I.; Schlamm, H. T.; Ji, X.; Stephens, J. M.; Tarallo, M.
Abstract: Objectives: To conduct a retrospective analysis of the association between drug tolerability and potential economic impact measured by medical resource utilization (MRU) for prophylaxis of invasive antifungal infections (IFI) after allogeneic hematopoietic stem cell transplantation (alloHCT). Methods: An open-label, multi-center study (IMPROVIT) included patients (≥12-years old) who were randomized to receive oral voriconazole (VOR) or oral itraconazole (ITR) from the alloHCT day for at least 100 days and up to 180 days. Trial data on discontinuation and MRU for the first 100 days were analyzed. Results: Two hundred and twenty-four patients were in VOR and 241 in ITR, with similar demographic distributions (average age of 43 years, 58% male, 92% Caucasian). All-cause and study drug intolerance discontinuations were less frequent with VOR than ITR (50% vs 63%, p  = 0.0137; 7% vs 22%, p  < 0.0001). VOR patients had longer study drug exposure (median = 96 vs 68 days, p  < 0.0001; mean = 68 vs 60 days, p  = 0.0044). ITR patients were 2-times more likely ( p  = 0.0110) to use other antifungals vs VOR patients. Controlling for treatment and key baseline variables, longer IFI prophylaxis was associated with fewer hospital days ( p  < 0.0001) and less other antifungal use ( p  < 0.0001). Patients who discontinued prophylaxis during the first 100 days incurred 10 more hospital days ( p  < 0.0001) and 17 more other antifungal days ( p  < 0.0001) compared to their counterparts. Eight more prophylaxis days were associated with ∼1 less hospital day and 3.6 less other antifungal days ( p  < 0.0001). Key limitation: MRU data collection was limited to the first 100 days post-transplant, which may not fully capture the real-world utilization and outcomes. Conclusions: Patients' ability to tolerate and continue their antifungal prophylaxis after alloHCT is associated with less use of MRU such as other antifungals and hospital days. In the current resource-constrained healthcare environment, it is important to consider the potential economic impact of the tolerability of antifungal prophylaxis.